How to Develop Leadership in The Context of Manufacturing? - Kravtšuk, Marina (Indonesian Journal of Sustainability Accounting and Management, 2024)
The study aims to replicate an earlier study and answer a research question: how to develop leadership in the real-life context of a Russian manufacturing organization. A 16-calendar week quasi- experiment with pre-and post-test design in a real-life context of a Russian manufacturing organization, involving three levels of managers, using MLQ with specified effectiveness criteria was conducted. The author acted as an immersed researcher. The results indicate that contextualization of leadership development intervention delivered a statistically significant shift in managers’ leadership styles and effectiveness with small to large effect sizes with a perspective of ensuring the sustainability of results. External validity of the study is ensured by replication of an earlier conducted study, method of “how to develop leadership in the real-life context” was explained, which can be replicated. Previously no similar studies were conducted in the hardware manufacturing industry of Russia, with the reported contextualization and explanation of “how to…”. Other studies of the same design and similar contexts are needed, transformational, environmental and social criteria could be added to the evaluation of effectiveness.